ผลของไคโตซานต่อการเจริญเติบโตของกล้วยไม้สกุลหวาย เอียสกุล Dendrobium Eiskul ในหลอดทดลอง - พานิษา พรเพียรภักดี (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Application of chitosan for stimulating growth and development in vitro of Dendrobium Eiskul tissue culture was investigated . The polymeric (P) and oligomeric (O) chitosan with 70, 80, or 90 degree of deacetylation (%DD) at various concentrations of 0, 10, 20, 40, or 80 ppm were added to the appropriate medium for Dendrobium tissue development. Polymeric chitosan with 70%DD (P70) 10 ppm, and P90 at 20 ppm added to modified VW liquid medium could significantly enhance plb multiplication,. All types of chitosan in this experiment when used up to 80 ppm had inhibitory effect on plb production. For the stage of plb development into plantlet, plbs were cultured in semi-solid modified VW medium. Addition of O80 chitosan at 20 ppm to the medium could significantly enhance plb and plantlet production. Approximately 1.6 times of plantlets, and 3.2 times of plbs were produced, when compared to the non-chitosan treatment control after 4-month maintenance. For the last step before exflasking, addition of O70 chitosan at 10 ppm to the medium showed the best result in shoot number and biomass production. O70 chitosan at 10 or 20 ppm was found to be the most appropriate chitosan molecule type and concentration for enhancing root development. This research indicated that chitosan of the appropriate molecular type, %DD and concentration for each stage of development could be used as a plant growth stimulant for Dendrobium Eiskul tissue culture in vitro.